Influence of Diamond Wire Saw Processing Parameters on the Sawn Surface Characteristics of Silicon Nitride Ceramics - Siyuan Zhang; Yufei Gao; Xingchun Zhang; Yufeng Guo (Micromachines, 2023)
For the slicing of superhard silicon nitride ceramics, diamond wire sawing technology has great potential for application, and its slicing surface characteristics are an important indicator of cutting quality. In this paper, the sawing experiments of silicon nitride ceramics were carried out within the range of industrial processing parameters of diamond wire sawing (saw wire speed: 800–1600 m/min, workpiece feed speed 0.1–0.4 mm/min). The effects of cutting parameters on the surface morphology, surface roughness and waviness of the as-sawn slices were analyzed. The results show that within the range of sawing parameters for industrial applications, the material on the diamond wire as-sawn surface of silicon nitride ceramics is removed mainly in a brittle mode, with the slice morphology showing brittle pits and regularly distributed wire marks in the 20–55 μm scale range. The surface roughness of the slices along the workpiece feed direction ranges from 0.27 to 0.38 μm and decreases with increasing saw wire speed and decreasing feed rate. The surface waviness ranges from 0.09 to 0.21 μm, which is in good agreement with the changing trend of the sliced-surface roughness. The results of the study provide an experimental reference for promoting the engineering application of diamond wire sawing technology to the processing of silicon nitride ceramic slices.